Utility of Farmer's Fallow Lands for Fodder Production with High Phenotypic Growth and Yield - Jalal, Nabilah; Khan, Md. Jasimuddin; Akbar, Md. Ali (Pakistan Journal of Nutrition, 2016)
Background: Land scarcity is increasing day by day in Bangladesh because of rising population and industrialization. The available limited land is used for food crop production especially rice production. As a result, only very limited land is available for fodder production. Objective: The study presents method of utilizing farmer’s fallow lands for fodder production to enhance availability of high quality fodder for their livestock. Materials and Methods: The treatments were replicated three times and the experiments were set up in Randomized Complete Block Design (RCBD). Duncan’s Multiple Range Test (DMRT) and Least Significant Difference (LSD) test were performed to evaluate the significance of mean differences among the treatments. This experiment was conducted with three fodders i.e., Napier, Splendida and Andropogon. Phenotypic growth and yield data were recorded for three cuttings. Results: Among the three fodders, plant height, leaf length, number of tiller per plant and yield values had significant variation (p